Исследование взаимосвязи физико-механических свойствалмазных шлифпорошков и эксплуатационных характеристик бурового инструмента - Богатырева, Г.П.; Ильницкая, Г.Д.; Петасюк, Г.А.; Богданов, Р.К.; Исонкин, А.М.; Закора, А.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Results of research of influence of physicomechanical properties of diamond powders on operational characteristics of the drill bits are considered. Essential influence durability characteristics of grains of synthetic diamonds on working capacity of the drill bits is experimentally confirmed. Analytical dependence of influence of physicomechanical properties of synthetic diamonds on working capacity of diamond drill bits is received.